Post-discharge surveillance of surgical site infections in teaching hospitals in Brazil - Amandha Fernandes,; Judith,; Vanessa De Brito, (Revista da Escola de Enfermagem da USP, 2021)
Objective: Understanding the reality of surgical site infections post-discharge surveillance in Brazilian teaching hospitals. Method: A cross-sectional study conducted by sending an online questionnaire to nurses from the Hospital Infection Control Committee of Brazilian teaching hospitals registered in the National Registry of Health Establishments. Results: Of the 193 teaching hospitals in Brazil, eight declined to take part as they did not conduct post-discharge surveillance and 36 did not respond. Twenty five of the remaining 149 hospitals provided detailed responses and 96% of responding institutions performed surgical site infection surveillance during hospitalization; active search (29.3%) was the main method, while 84% reported performing post-discharge surveillance mainly by telephone (42.8%). Both surveillance actions have nurses as the main responsible professionals. Conclusion: Nurses play a prominent role in surgical site infection identification/screening actions, and active search during hospitalization allied with post-discharge surveillance by telephone were the preferred methods.